Frequency of Cataract in Diabetic Verses Non-Diabetic Patients - Khurram Nafees, Kiran Aslam, Muhammad Sufyan, Aneeq Ansari, Imran Khalid (Pakistan Journal of Ophthalmology, 2019)
Purpose: To determine the frequency of cataract in diabetic verses non-diabetic patients. Study Design: Descriptive cross-sectional study. Place and Duration of Study: Eye Outpatients Department of Fatima Memorial Hospital Lahore from December to March 2018. Material and Methods: Patients between 20-50 years of age with and without diabetes were included in the study. The diabetic patients included in the study had diabetes for at least 6-7 years. Patients with any other systemic disease and patients <20 years and > 50 years were excluded from the study. All patients underwent a complete eye examination including uncorrected and best corrected visual acuity, refraction, dilated slit lamp and fundus examination. Results: A total of 194 patients were examined. Average duration of diabetes was 6-7 years with age groups 20-35 years (34.02%) and 35-50 years (65.97%). There were 79 (79.79%) patients with diabetes who had cataract while only 13 (13.68%) non- diabetic patients had cataract. Most common type of cataract in diabetic patients was posterior subcapsular cataract (PSCC) 43 (54.43%). This was followed by nuclear cataract in 17 (21.51%) and cortical cataract in 14 (17.72%) patients. While in non-diabetic patients nuclear cataract was seen in 6 (46.15%) patients and cortical and PSCC were the same percentage 3 (23.07%). Cataract frequently developed in the age group of 35-50 years in diabetic patients. Conclusion: Diabetic patients should be screened for cataract early as PSCC can cause significant deterioration of vision between 35-50 years. Keywords: Cataract, Diabetes Mellitus (DM), Posterior Sub Capsular Cataract (PSCC), Nuclear Cataract (NC) and Cortical Cataract (CC).